Hidden Multilingualism in 19th-Century European Literature Traditions, Texts, Theories - Mende, Jana-Katharina (De Gruyter, 2023)
This volume provides a new set of methodological and theoretical approaches to the study of literary multilingualism in the age of national literature. Broader studies examine multilingual origins of seemingly monolingual national literatures. Case studies show that supposedly monolingual authors used multilingual techniques in their writing. The last part presents methods and theories to analyse multilingual texts within national literatures.